2015
DOI: 10.1002/gj.2634
|View full text |Cite
|
Sign up to set email alerts
|

U–Pb dating of detrital zircons from Andros, Greece: constraints for the time of sediment accumulation in the northern part of the Cycladic blueschist belt

Abstract: The Attic–Cycladic Crystalline Belt in the central Aegean region represents a major tectono‐stratigraphic unit of the Hellenides. The essential geological, magmatic and tectono‐metamorphic features are well documented. Unresolved questions concern the time of sediment accumulation and litho‐ and/or tectono‐stratigraphic relationships across the study area. In order to address this issue we have studied siliciclastic metasedimentary rocks from Andros Island, northern Cyclades. The sampling strategy aimed at cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 61 publications
0
27
0
Order By: Relevance
“…However, the exact tectonic setting for the deposition of CBU protoliths remains contentious and centers around the nature of the Pindos Basin (e.g., Bortolotti et al, ; Menant, Jolivet, & Vrielynck, ; Papanikolaou, , ; Stampfli et al, ; Tremblay et al, ; van Hinsbergen, Hafkenscheid, et al, ; van Hinsbergen, Zachariasse, et al, ; van Hinsbergen & Schmid, ). The ages of intercalated volcanic rocks and DZ studies in the western and northern Cyclades demonstrated that CBU deposition spanned from Triassic to Paleogene (Bröcker et al, ; Henjes‐Kunst & Kreuzer, ; Hinsken et al, ; Keay, ; Löwen et al, ; Seman et al, ) and was likely initially accumulated along a rifted continental margin (Seman et al, ). In the southern and central Cyclades, Fu et al () demonstrated that the CBU contains Middle Triassic zircon characterized by rift‐related δO 18 and εHf values.…”
Section: Geologic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact tectonic setting for the deposition of CBU protoliths remains contentious and centers around the nature of the Pindos Basin (e.g., Bortolotti et al, ; Menant, Jolivet, & Vrielynck, ; Papanikolaou, , ; Stampfli et al, ; Tremblay et al, ; van Hinsbergen, Hafkenscheid, et al, ; van Hinsbergen, Zachariasse, et al, ; van Hinsbergen & Schmid, ). The ages of intercalated volcanic rocks and DZ studies in the western and northern Cyclades demonstrated that CBU deposition spanned from Triassic to Paleogene (Bröcker et al, ; Henjes‐Kunst & Kreuzer, ; Hinsken et al, ; Keay, ; Löwen et al, ; Seman et al, ) and was likely initially accumulated along a rifted continental margin (Seman et al, ). In the southern and central Cyclades, Fu et al () demonstrated that the CBU contains Middle Triassic zircon characterized by rift‐related δO 18 and εHf values.…”
Section: Geologic Backgroundmentioning
confidence: 99%
“…The Cycladic Blueschist Unit (CBU), which lies at the heart of the Attic‐Cycladic subduction complex, has been the focus of numerous studies constraining its prograde and retrograde HP‐LT metamorphic evolution and exhumation, especially on the islands of Syros and Sifnos where HP‐LT blueschist facies rocks are excellently preserved alongside younger greenschist to amphibolite facies (e.g., Avigad & Garfunkel, ; Behr et al, ; Dürr et al, ; Grasemann et al, ; Grasemann et al, ; Jolivet et al, ; Laurent et al, ; Philippon et al, ; Soukis & Stockli, ). However, limited detailed work exists about the chronostratigraphy, the depositional history, or the paleogeographic and tectonic evolution of the CBU or Cycladic Basement (CB) protoliths, consequently hampering insights into subduction processes, the juxtaposition of different HP‐LT units, and Aegean exhumation history (e.g., Bröcker et al, ; Bröcker & Pidgeon, ; Fu et al, ; Henjes‐Kunst & Kreuzer, ; Hinsken et al, ; Keay, ; Keay & Lister, ; Löwen et al, ; Poulaki et al, ; Seman et al, ). In particular, little is known about the structurally lowest unit, the CB, which represents a fragment of Adria/Pelagonia continental crust underlying the CBU in the southern Cyclades (Jolivet & Brun, ; Ring et al, ; Stampfli et al, ; Stampfli & Borel, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar maximum deposition ages were considered for the Lower Unit in Andros (Bröcker et al, ). Yet in the Makrotantalon Unit of Andros (Bröcker et al, ; Papanikolaou, ), Permian (ca. 260‐Ma) depositional ages and fossils were defined, although the tectonostratigraphic position of this unit is not very clear.…”
Section: Previous Studies and Geological Settingsmentioning
confidence: 99%
“…The Cover Series section is made of predominantly Mesozoic marine metasediments, typically represented by metapelites in intercalation with metabasic intrusions, Triassic metatuffs, and Triassic-Jurassic marble horizons (the latter are more substantial in the Southern Cyclades), as well as metabasites, eclogites, and metaperidotites that originated from the subducting crust of a Late Mesozoic oceanic basin (e.g., Bröcker et al, 2016;Bröcker & Pidgeon, 2007;Dürr et al, 1978;Fu et al, 2015;Hinsken et al, 2016;Keay, 1998;Melidonis, 1980;Okrusch & Bröcker, 1990;Ring et al, 2010). The lowermost part of the Cover Series of the Lower Unit in Naxos was deposited in the Late Triassic (200-220 Ma; Keay, 1998;Dürr et al, 1978;Papanikolaou, 1978).…”
Section: 1029/2018tc005046mentioning
confidence: 99%
See 1 more Smart Citation